Profiles of multidrug-resistant organisms among patients with bacteremia in intensive care units: an international ID-IRI survey - El-Sokkary, Rehab; Uysal, Serhat; Erdem, Hakan; Kullar, Ravina; Pekok, Abdullah Umut; Amer, Fatma; Rello, Jordi (Springer, 2021)
Evaluating trends in antibiotic resistance is a requisite. The study aimed to analyze the profile of multidrug-resistant organisms (MDROs) among hospitalized patients with bacteremia in intensive care units (ICUs) in a large geographical area. This is a 1-month cross-sectional survey for blood-borne pathogens in 57 ICUs from 24 countries with different income levels: lower-middle-income (LMI), upper-middle-income (UMI), and high-income (HI) countries. Multidrug-resistant (MDR), extensively drug-resistant (XDR), or pan-drug-resistant isolates were searched. Logistic regression analysis determined resistance predictors among MDROs. Community-acquired infections were comparable to hospital-acquired infections particularly in LMI (94/202; 46.5% vs 108/202; 53.5%). Although MDR (65.1%; 502/771) and XDR (4.9%; 38/771) were common, no pan-drug-resistant isolate was recovered. In total, 32.1% of MDR were Klebsiella pneumoniae, and 55.3% of XDR were Acinetobacter baumannii. The highest MDR and XDR rates were in UMI and LMI, respectively, with no XDR revealed from HI. Predictors of MDR acquisition were male gender (OR, 12.11; 95% CI, 3.025-15.585) and the hospital-acquired origin of bacteremia (OR, 2.643; 95%CI, 1.462-3.894), and XDR acquisition was due to bacteremia in UMI (OR, 3.344; 95%CI, 1.189-5.626) and admission to medical-surgical ICUs (OR, 1.481; 95% CI, 1.076-2.037). We confirm the urgent need to expand stewardship activities to community settings especially in LMI, with more paid attention to the drugs with a higher potential for resistance. Empowering microbiology laboratories and reports to direct prescribing decisions should be prioritized. Supporting stewardship in ICUs, the mixed medical-surgical ones in particular, is warranted.
Keywords: Multidrug resistance; Infection control; Stewardship; Low- and upper-middle and high income; XDR; Pan-drug resistance